Practical Model to Optimize the Strategy of Adjuvant Postmastectomy Radiotherapy in T1-2N1 Breast Cancer With Modern Systemic Therapy - Xu, Fei-Fei; Cao, Lu; Xu, Cheng; Cai, Gang; Wang, Shu-Bei; Qi, Wei-Xiang; Chen, Jia-Yi (Frontiers in Oncology, 2022)
Purpose: The effect of adjuvant irradiation after mastectomy in early-stage breast cancer patients remains controversial. The present study aims to explore the clinical benefit obtained from adjuvant radiotherapy among post-mastectomy pT1-2N1 breast cancer patients who received adjuvant modern systemic therapy. Methods: Medical records of consecutive patients with pT1-2N1 breast cancer who received mastectomy in our institution between Jan 2009 and Dec 2016 were retrospectively reviewed. High-risk features comprising patient age, number of positive lymph nodes, T stage and Ki67 index, which were developed previously at our institution using early-stage breast cancer patients after mastectomy without adjuvant radiotherapy. Differences of survival and local recurrence were compared between no-postmastectomy radiotherapy (PMRT) and PMRT group according to number of risk factors. The time-to-event curves were calculated by the Kaplan-Meier methods and compared by the log-rank test. Propensity score matching (PSM) was performed to reduce the imbalances in patient characteristics. Results: A total of 548 patients were enrolled (no-PMRT: 259 and PMRT: 289). After a median follow-up of 69 months, the 5-year rate of DFS, BCSS and LRR in overall cohort were 90.2%, 97.4% and 3.6%, respectively. PMRT did not significantly improve DFS, BCSS and LRRFS in the whole cohort. Patients were divided into low- (with no or one risk factor) and high-risk (with two or more risk factors) groups. According to the univariable and multivariable analysis, high-risk group (HR=1.81, 95% CI 1.11-2.98, p=0.02) was demonstrated as an independent risk factor for DFS. For high-risk group, PMRT significantly improved DFS from 81.4% to 91.9% and BCSS from 95.5% to 98.6% and decreased the 5-year rate of LRR from 5.6% to 1.4%, respectively (p<0.01, p=0.05 and p=0.06). However, no survival benefit from PMRT was observed in low-risk group in terms of DFS, BCSS and LRR (p=0.45, p=0.51 and p=0.99, respectively). In multivariate analysis, PMRT remained an independent prognostic factor for DFS (HR=0.50, 95% CI 0.24-1.00, p=0.05) in high-risk group. After PSM analysis, the survival benefit of PMRT sustained in high-risk patients. Conclusion: PMRT significantly improved DFS in high-risk pT1-2N1 breast cancer patients, but not in low-risk patients. Independent validation of our scoring system is recommended.